Probation - Canton, Rob (Routledge, Taylor & Francis Group, 2018)
chapter Introduction -- chapter 1 Probation and criminal justice -- chapter 2 Probation’s histories -- chapter 3 Probation values, justice and diversity -- chapter 4 Punishment, sentencing and probation -- chapter 5 Community sentences and probation’s contribution to sentencing -- chapter 6 Probation in other countries -- chapter 7 The supervision of offenders: What works -- chapter 8 Desistance, good lives, compliance and motivation -- chapter 9 Probation, risk and public protection -- chapter 10 Probation practice: Offender management -- chapter 11 Probation practice: The ASPIRE model -- chapter 12 Community Service -- chapter 13 Probation and prison -- chapter 14 Victims, probation and criminal justice -- chapter 15 Local and national, public and private -- chapter 16 Probation staff and culture.